Effects of permafrost degradation on water and sediment quality and heterotrophic bacterial production of Arctic tundra lakes: An experimental approach. (27th May 2015) - Moquin, Paul A.; Wrona, Frederick J.
Abstract: To assess the effects of shoreline retrogressive thaw slumping on the chemical, physical, and ecological components of small tundra lakes, an in situ manipulative mesocosm experiment was performed in an upland, unslumped Arctic lake located near Inuvik, Northwest Territories, Canada. Twelve replicate mesocosms were established: three control and three replicates of three treatment levels each dosed with differing amounts of soil sourced from the thaw scar of a nearby lake affected by shoreline retrogressive thaw slumping. The soil was rich in ionic compounds such as calcium, magnesium, and sulfates reflecting the marine origin of the local geology, and also contained nutrients (P and N) and organic carbon. Water column ionic and nutrient concentrations increased with increasing soil input, while pelagic bacterial production decreased. Conversely, benthic bacterial production increased by 44, 112, and 498% in the low, medium, and high soil treatments, respectively. This study shows thermokarst slumping to differentially affect pelagic and benthic heterotrophic microbial production through changes to the physical and chemical properties of the water and sediment. The stimulation of benthic and corresponding inhibition of pelagic heterotrophic productivity relative to the control treatments over the 12‐week experimental period indicate that shoreline retrogressive thaw slumping alters heterotrophic energy pathways during the early successional stages of thermokarst lakes experiencing shoreline slumping.